Alfonso de Valdés: španělský humanista ve službách císaře Karla V. - Jiří Sucharda (Historie - Otázky - Problémy, 2022)
The main purpose of this text is to present the life and work of Spanish humanist and the secretary of the emperor Charles V, Alfonso de Valdés. The text deals primarily with the role of Valdés in the propagation of the idea of a “universal monarchy”, his relationship with the grand chancellor of Charles V Mercurino di Gattinara, as well as with his reflection of the beginning of the Protestant movement, especially in the context of his role as one of the negotiators during the imperial diet in Augsburg in 1530.